Implementasi Contextual Teaching and Learning (CTL) untuk Meningkatkan Critical Thinking dalam Pembelajaran Materi Agama Islam - Winanda Arfian (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2024)
Critical thinking skills are essential to face the development of the 21st century. One of the learning models that can develop critical thinking skills is Contextual Teaching and Learning (CTL). The purpose of this study is to analyze the implementation of Contextual Teaching and Learning in improving critical thinking skills in Islamic Religious Education subjects. This research was conducted using the Systematic Literature Review (SLR) method. The literature reviewed in this article amounted to eight articles found on Google Scholar, with details of five journal articles, two theses, and one thesis. The results of the study showed that the implementation of Contextual Teaching and Learning in the Islamic Religious Education learning process dominated student-centered learning by directing students to discuss problems in real life that were presented. This was able to improve critical thinking skills and problem solving. Contextual Teaching and Learning had a positive impact on improving critical thinking.